Research on multi-phase flow test and flow simulation test in energy enterprise automation - Liang, Ying; Wang, Jinxi (Frontiers in Energy Research, 2022)
Abstract:In the process of oil extraction and transportation, due to the interaction between oil, gas and water, hydrates are easily generated and pipelines are blocked. Based on this, from the perspective of energy enterprise automation technology, testing and research on oil and gas multiphase flow models and flow models are carried out. The hydrate formation area is analyzed by using the hydrate formation phase equilibrium theory, and the formation rate, deposition characteristics and blockage formation mechanism are analyzed. The influence of phase flow and heat transfer; after the boundary interface coefficient between oil, gas and water is clarified, a multiphase flow model of oil, gas and water is established. In the experimental test, the differential pressure signal is used to carry out the research on the oil and gas multiphase flow model and flow model, and it is concluded that the minimum critical superficial liquid velocity among the three flow patterns of oil, water and gas is 0.113 m/s, It can clearly characterize the characteristics of the flow pattern transition, which has certain practical significance for the sustainable development of energy enterprises.